2003
DOI: 10.1002/chin.200334143
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Synthesis of 2,9‐Disubstituted 8‐Hydroxyadenine Derivatives.

Abstract: Purine derivativesPurine derivatives R 0540 Efficient Synthesis of 2,9-Disubstituted 8-Hydroxyadenine Derivatives. -A novel synthesis of 8-hydroxyadenine derivatives is developed using compounds (IV) as key intermediates. Treatment of (XXI) with urea and subsequent alkylation results in the formation of (XIX) in an alternative method. Under mild conditions, various types of substituents are directly introduced at the 2-and 9-positions of the 8-hydroxyadenine nucleus. -(HIROTA*, K.; KAZAOKA, K.; NIIMOTO, I.; SA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0
1

Year Published

2004
2004
2007
2007

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 1 publication
0
4
0
1
Order By: Relevance
“…Chemie einem Eintopfverfahren weiterentwickelt, [104] bei dem eine In-situ-Aktivierung des Pd/C-Katalysators durch Wasserstoff stattfindet. [105] Folgerichtig wurde in wasserstofffreier Atmosphäre bei der Modellverbindung Diphenylmethan (99) Weiterführende Untersuchungen von Sajiki et al an 5-Phenylvaleriansäure (102) offenbarten darüber hinaus einen starken Einfluss der Reaktionstemperatur auf Regioselektivität und Deuteriumeinbau beim H/D-Austausch.…”
Section: Methodsunclassified
“…Chemie einem Eintopfverfahren weiterentwickelt, [104] bei dem eine In-situ-Aktivierung des Pd/C-Katalysators durch Wasserstoff stattfindet. [105] Folgerichtig wurde in wasserstofffreier Atmosphäre bei der Modellverbindung Diphenylmethan (99) Weiterführende Untersuchungen von Sajiki et al an 5-Phenylvaleriansäure (102) offenbarten darüber hinaus einen starken Einfluss der Reaktionstemperatur auf Regioselektivität und Deuteriumeinbau beim H/D-Austausch.…”
Section: Methodsunclassified
“…However, such conventional procedures for the incorporation of deuterium into the C−H bonds of organic compounds are often limited to activated positions of the molecules, leading to low levels of deuterium incorporation, and usually require a vast amount of the catalyst, addition of acidic or basic additives, and/or deuterium atmosphere. Although, most recently, Matsubara et al, reported a remarkable H−D exchange transformation with 10% Pd/C in subcritical D 2 O (250 °C) in the absence of hydrogen, we independently found that hydrogen gas is essential for the 10% Pd/C-catalyzed H−D exchange reaction below 180 °C. , …”
mentioning
confidence: 47%
“…18 we independently found that hydrogen gas is essential for the 10% Pd/C-catalyzed H-D exchange reaction below 180 °C. 19,20 We report here that a heterogeneous Pd/C-D 2 O-H 2 system efficiently catalyzes the exchange of deuterium from D 2 O into organic compounds, including nonactivated positions of the molecules.…”
mentioning
confidence: 99%
See 2 more Smart Citations